Embryo transfer practices and perinatal outcomes by insurance mandate status - Boulet, Sheree L. (Fertil Steril, 2015)
OBJECTIVE: To use linked assisted reproductive technology (ART) surveillance and birth certificate data to compare ET practices and perinatal outcomes for a state with a comprehensive mandate requiring coverage of IVF services versus states without a mandate. DESIGN: Retrospective cohort study. SETTING: Not applicable. PATIENT(S): Live-birth deliveries ascertained from linked 2007–2009 National ART Surveillance System and birth certificate data for a state with an insurance mandate (Massachusetts) and two states without a mandate (Florida and Michigan). INTERVENTION(S): None. MAIN OUTCOME MEASURE(S): Number of embryos transferred, multiple births, low birth weight, preterm delivery. RESULT(S): Of the 230,038 deliveries in the mandate state and 1,026,804 deliveries in the nonmandate states, 6,651 (2.9%) and 8,417 (0.8%), respectively, were conceived by ART. Transfer of three or more embryos was more common in nonmandate states, although the effect was attenuated for women 35 years or older (33.6% vs. 39.7%; adjusted relative risk [RR], 1.46; 95% confidence interval [CI], 1.17–1.81) versus women younger than 35 (7.0% vs. 26.9%; adjusted RR, 4.18; 95% CI, 2.74–6.36). Lack of an insurance mandate was positively associated with triplet/higher order deliveries (1.0% vs. 2.3%; adjusted RR, 2.44; 95% CI, 1.81–3.28), preterm delivery (22.6% vs. 30.7%; adjusted RR, 1.31; 95% CI, 1.20–1.42), and low birth weight (22.3% vs. 29.5%; adjusted RR, 1.28; 95% CI, 1.17–1.40). CONCLUSION(S): Compared with nonmandate states, the mandate state had higher overall rates of ART use. Among ART births, lack of an infertility insurance mandate was associated with increased risk for adverse perinatal outcomes.